Propuesta de implementación de seguridad y protección de datos de pacientes en la telemonitorización de la marcha mediante IoT (2021)
The internet of things (IoT) is an emerging technology where sensor measurement capacity and the existing internet converge, with potential application in the health area and especially in telemonitoring. Telemonitoring is one of the modalities of telemedicine, which requires the registration, storage and transmission of patient information and biomedical parameters related to the health service. According to resolution 2654 of 2019, this modality must ensure the quality of the data through technological platforms or electronic devices, which includes strengthening the security and protection of patient data, and guaranteeing four objectives: authenticity, integrity, availability and reliability, in such a way that the integrity of the people is guaranteed. This work presents the design and implementation of a prototype of an IoT system that guarantees data security with application in the telemonitoring of gait variables. This system consists of an application developed in Matlab and installed on an Android mobile device, which is used for the acquisition of kinematic information through the cell phone's accelerometer, its processing and its safe delivery to the cloud on the ThingSpeak platform, to be able to be viewed and analyzed remotely. The verification of the measurements obtained was carried out using the Kinovea software, obtaining an error of 5% and the system was implemented to guarantee security for IoT systems. Finally, a system validation was carried out to monitor the gait cadence variable in a protocol carried out for a week, verifying that the information can be viewed and processed remotely on the ThingSpeak server.